Qualitative and quantitative proteomic analysis of Vitamin C induced changes in Mycobacterium smegmatis - Mishra, Abhishek; Sarkar, Dhiman (Frontiers in Microbiology, 2015)
Vitamin C is a critical dietary nutrient in human which has a wide range of regulatory effects on gene expression and physiology of Mycobacterium tuberculosis that leads to a dormant drug-tolerant phenotype. In the presence of iron, vitamin C shows a high bactericidal activity even in the drug resistant phenotype of M. tuberculosis. The regulatory mechanisms underlying vitamin C induced adaptations are largely unknown due to lack of functional genomics data in this field. In this study, we attempt to characterize the direct affect of vitamin C treatment on the physiology of actively growing Mycobacterium smegmatis. The study chose M. smegmatis as it is a fast-growing bacterium and a non-pathogenic model system which shares many physiological features with the pathogenic M. tuberculosis including dormancy and its regulation. The proteomic adaptation of M. smegmatis on vitamin C treatment demonstrates the important changes in cellular and metabolic process such as reversal of tricarboxylic acid cycle, decrease in ATP synthesis, decrease in iron acquisition and storage, and induction of dormancy regulators WhiB3, PhoP and Lsr2.